Equivalential Algebras with Conjunction on Dense Elements - Przybyło, Sławomir; Słomczyńska, Katarzyna (Bulletin of the Section of Logic, 2022)
We study the variety generated by the three-element equivalential algebra with conjunction on the dense elements. We prove the representation theorem which let us construct the free algebras in this variety.